(untitled) (Anwer Khan Modern Medical College Journal, 2020)
Background and objectives: Chronic kidney disease (CKD), an important, chronic, noncommunicable disease is now one of the major public health problems in our country. Early detection of CKD is crucial to prevent its progression, and thereby, to potentially improve its outcome. Number of young patients with CKD are increasing day by day. Only a few studies are done in our country to assess etiology of CKD in young patients. This study was aimed to assess the etiology of CKD in young patients. Materials and Methods: Data were collected from 150 patients of CKD between 15- and 40-years age who presented to Jahurul Islam Medical College Hospital, Kishoregonj from Jan 2015 to Dec 2019. They were clinically evaluated and underwent relevant investigations including renal biopsy in indicated cases. Results: In this study, there was an overall male preponderance (60.67%) with age range of 31-35 years (32%). Most common symptoms of presentation were related to gastrointestinal disturbances (70%), breathlessness (66%), easy fatigability (62%), and urinary disturbances (56%). Pallor, pedal edema and facial puffiness were major clinical features. Small kidneys were seen in 65.33% of patients. 90 % of patients had proteinuria. Majority (46.67%) had CKD of unknown etiology. In this unknown etiology patients, most of them were found to have chronic glomerulonephritis based on clinical presentation and other supporting investigations. Diabetic nephropathy and obstructive uropathy were found in 13.33% patients. 80% patients were presented in stage IV and stage V CKD. Histopathologically, etiology was proven among 46 patients (30.67%) with renal biopsy. Conclusion: It is concluded that male patients in the second and third decades were in the majority requiring medical care. Chronic Glomerulonephritis of unknown causes constitutes a major etiology among the young presenting in late stages of CKD. AKMMC J 2020; 11(2) : 124-127